Association between the increased thoracic curvature and the prevalence of pain in the shoulder complex on roping practitioners - Santos, Analícia Bracho; Dhein, William; Torre, Marcelo La (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: The roping practice is a sporting the practitioner aims to throw a type of rope with a loop over the head or around the horns of the steer during the horse riding. The movement of looping is performed by repeated rotations of the shoulder above the shoulder girdle line, and this action, associated with changes in the thoracic spine, can overwhelm the structures of the shoulder complex and the muscles. Objective: Analyze the association between changes in increased thoracic curvature and the prevalence of pain in the shoulder complex in roping practitioners. Methods: The sample was intentionally with 20 male roping practitioners who were submitted to assessment of shoulder pain using the shoulder pain and disability index (spadi), three shouder’s orthopedic test, the jobe’s test, the yergason’s test, the neer’s test, and also the measurement of the thoracic curvature angle through the flexicurve method. The statistical data were processed using the SPSS version 20.0, and the Chi-Squared test was applied to evaluate the association between the variables. The level of significance adopted was 5%. Results: 70% of the sample presented pain in the shoulder joint complex and 45% of the practitioners presented hyperkyphosis. There is a moderate association between the variables (p = 0.008 / contingency coefficient = 0.510). Conclusion: The results showed a moderate association between the prevalence of pain in the shoulder complex and the increase of the thoracic curvature angle.